Health-Related Physical Activity Levels in Spanish Youth and Young Adults. Issue 1 (February 2014) - Cocca, Armando; Liukkonen, Jarmo; Mayorga-Vega, Daniel; Viciana-Ramírez, Jesús
The aim of this study was to analyze the current physical activity (PA) levels in youth and young adults from Granada, Spain, and to assess if they accomplish the recommendations for healthy PA. A sample of 1, 832 boys and 1, 840 girls was administered the International Physical Activity Questionnaire. Results showed that most of the children (72.2%) and adolescents (56.4%) reached the recommended PA levels, whereas only 40% of young adults achieved recommended levels of PA. The most active were students from Primary schools, whereas university students were the least active. Youth of college and university ages were found to be at higher risk for engagement in PA.